2021
DOI: 10.1002/jlb.2a1220-824r
|View full text |Cite
|
Sign up to set email alerts
|

miR-181c regulates MCL1 and cell survival in GATA2 deficient cells

Abstract: GATA2 is a transcription factor critical for hematopoiesis. Germline mutations in GATA binding protein 2 (GATA2) led to haploinsufficiency, severe cytopenias of multiple cell lineages, susceptibility to infections and strong propensity to develop myelodysplastic syndrome, and acute myeloid leukemia. Mechanisms of progressive cytopenias remain unclear. MicroRNA (miRNA) represents a unique mechanism of post-transcriptional gene regulation. In this study, miRNA profiles were evaluated and eight miRNAs were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Consistently, analysis of two publicly available datasets GSE108901 and GSE66186, which contained miRNA expression data mainly from Western CLL patients and Western normal individuals, also showed higher expression of pro-CLL miR-4485 and lower expression of the CLL-suppressive miRNA in CLL patients compared with healthy individuals (Online Supplementary Figure S4). Since the five miRNA identified in Figure 2B (miR-181d, miR-181c, miR-363, miR-138, and miR-181a) with putative anti-CLL function had been reported previously, 23,[28][29][30][31][32][33][34] whereas miR-4485 was the only microRNA identified as a putative CLL-promoting molecule with high expression in CLL cells in both ethnic groups and a downregulation in Asian normal B lymphocytes, we thus focused our efforts on investigating the role of miR-4485. In order to investigate the functional impact of miR-4485 on CLL cells, we first used a lentiviral There was a significant decrease in cell proliferation after MEC1 or MEC2 cells were transfected to express miR-4485 antagonist, whereas transfection using the control vector did not affect cell proliferat6ion (Figure 3B).…”
Section: High Expression Of Mir-4485 Promotes Chronic Lymphocytic Leu...mentioning
confidence: 61%
“…Consistently, analysis of two publicly available datasets GSE108901 and GSE66186, which contained miRNA expression data mainly from Western CLL patients and Western normal individuals, also showed higher expression of pro-CLL miR-4485 and lower expression of the CLL-suppressive miRNA in CLL patients compared with healthy individuals (Online Supplementary Figure S4). Since the five miRNA identified in Figure 2B (miR-181d, miR-181c, miR-363, miR-138, and miR-181a) with putative anti-CLL function had been reported previously, 23,[28][29][30][31][32][33][34] whereas miR-4485 was the only microRNA identified as a putative CLL-promoting molecule with high expression in CLL cells in both ethnic groups and a downregulation in Asian normal B lymphocytes, we thus focused our efforts on investigating the role of miR-4485. In order to investigate the functional impact of miR-4485 on CLL cells, we first used a lentiviral There was a significant decrease in cell proliferation after MEC1 or MEC2 cells were transfected to express miR-4485 antagonist, whereas transfection using the control vector did not affect cell proliferat6ion (Figure 3B).…”
Section: High Expression Of Mir-4485 Promotes Chronic Lymphocytic Leu...mentioning
confidence: 61%
“…miRNAs have been confirmed to modulate mRNA expression by inhibiting mRNA translation 18,19 . Previous reports have shown that miRNAs are able to play as a critical modulator in the progression of CRC.…”
Section: Introductionmentioning
confidence: 97%
“…miRNAs have been confirmed to modulate mRNA expression by inhibiting mRNA translation. 18,19 Previous reports have shown that miRNAs are able to play as a critical modulator in the progression of CRC. Wang et al revealed that miR-22-3p suppressed the growth of CRC cells through downregulation of PI3K/Akt signaling.…”
Section: Introductionmentioning
confidence: 99%